2003
DOI: 10.1097/01.sap.0000067726.32731.e1
|View full text |Cite
|
Sign up to set email alerts
|

Stabilized Autologous Fibrin-Chondrocyte Constructs for Cartilage Repair in Vivo

Abstract: Stabilization of fibrin-chondrocyte constructs with fibrinolytical inhibitors has been shown to be a feasible method for the reconstruction of cartilage in vitro. In this study, the method was tested in vivo. Autologous cultures were used to form stabilized fibrin-chondrocyte constructs that were injected into auricular cartilage defects of rabbits. Stabilization was achieved by high doses of fibrinolytic inhibitors. Samples were prepared for magnetic resonance imaging, histology, and immunohistochemistry afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(48 citation statements)
references
References 30 publications
0
47
0
Order By: Relevance
“…Fibrin gels have already been used in cardiovascular and thoracic surgery and as a delivery system for drugs. They have also been proven successful in the transplantation of chondrocytes (Fortier et al 2002;Fussenegger et al 2003;Hendrickson et al 1994, Nixon et al 1999Westreich et al 2004). Although the fibrin gel is a natural scaffold with many advantages, its main drawback is fibrinolysis.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Fibrin gels have already been used in cardiovascular and thoracic surgery and as a delivery system for drugs. They have also been proven successful in the transplantation of chondrocytes (Fortier et al 2002;Fussenegger et al 2003;Hendrickson et al 1994, Nixon et al 1999Westreich et al 2004). Although the fibrin gel is a natural scaffold with many advantages, its main drawback is fibrinolysis.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, fibrin gels can be produced into an injectable, moldable form minimizing invasive implantation (Passaretti et al 2001;Silverman et al 1999;Westreich et al 2004;Xu et al 2004). Previous studies have also shown that fibrin gels are capable of supporting cartilage formation of chondrocytes (Fortier et al 1997(Fortier et al , 1998(Fortier et al , 2002Fussenegger et al 2003, Hendrickson et al 1994Nixon et al 1999;Meinhart et al 1999;Passaretti et al 2001;Silverman et al 1999;Sims et al 1998;Westreich et al 2004;Xu et al 2004) and chondrogenic and osteogenic transformation of mesenchymal stem cells (Bensaid et al 2003;Worster et al 2001). However, fibrin is intrinsically unstable due to fibrinolysis.…”
Section: Introductionmentioning
confidence: 86%
“…Wang et al, 2010a;W. Wang et al, 2010b), or by the use of enzymatic inhibitors (Fussenegger et al, 2003). Eyrich et al reported some optimized conditions that lead to fibrin gels that were stable for up to three weeks in vitro (Eyrich et al, 2007).…”
Section: Fibrinmentioning
confidence: 99%
“…Alginate and agarose are polysaccharide biomaterials that originate from seaweed and show good biocompatibility and cytocompatibility; however, their poor degradation kinetics and limited potential for functional modification limits their clinical use (Murphy and Sambanis 2001). Fibrin is another natural scaffold that is derived from blood and has been shown to modulate cartilage formation in vivo by facilitating the adhesion of chondrocytes (Fussenegger et al 2003). Nevertheless, fibrin is mechanically inadequate for cartilage tissue engineering, and its degradation rate is unstable.…”
Section: Natural and Synthetic Scaffoldsmentioning
confidence: 99%